AC-Impedance, Dynamic mechanical analysis and DSC investigations on poly(methyl methacrylate)–LiTf polymer electrolyte systems (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Gel polymer electrolytes synthesized from Poly(methylmethacrylate) (PMMA) as the host, ethylene carbonate (EC)/propylene carbonate (PC) as plasticizer and LiCF3SO3 (LiTf) as a salt has been prepared using solution casting technique. X-ray characterization confirms the complete dissociation of the LiTf salt in the gel polymer. The effect of LiTf salt on ionic conductivity, ionic transference number (tion) and mechanical characteristics were investigated. The ac impedance has been studied to evaluate the ionic conductivity. It was observed that the ionic conductivity of the prepared gel reached the highest value of  6.60 x 10-5 S/cm at 10.2 wt.% (1M) of LiTf salt. The temperature dependence studies showed that the samples were ionic conductors and seemed to obey the Vogel Tamman Fulcher (VTF) rule.  Dynamic mechanical  analysis (DMA) indicates that  the LiTf salt induces a remarkable increase in the storage modulus of the matrix at temperatures above the glass transition (rubbery plateau region).